Effect of a skirted mudmat foundation on local scour around a submerged structure. (15th December 2020) - Yao, Weidong; Draper, Scott; An, Hongwei; Cheng, Liang; Harris, John M.; Whitehouse, Richard J.S.
Abstract: In this paper, local scour around a subsea structure supported by a skirted mudmat foundation is explored experimentally. For simplicity the structure is represented as a submerged circular cylinder founded on a concentric circular mudmat. The experiments are conducted in the clear-water regime and various geometries are considered by varying the height of the submerged cylinder relative to its diameter h 1 / D 1, and the diameter of the mudmat relative to the submerged cylinder D 2 / D 1 . The experimental results indicate that the scour process can be categorized into two modes depending on geometry: Mode 1, in which local scour develops immediately at the upstream side of the mudmat; and Mode 2, in which local scour initiates at the downstream side of the mudmat and propagates upstream. For each mode, the rate of scour reduces as the mudmat becomes relatively large (i.e. as D 2 / D 1 increases). This reduction is most significant if the mudmat size is sufficient to swap the mode of scour from Mode 1 to Mode 2. The reduction in scour rate, however, does not coincide with a reduction in maximum scour depth. Instead, the relative scour depth of the superstructure S / D 1 increases as the mudmat becomes larger (i.e. as D 2 / D 1 increases). This trend is quantitatively explained by considering the effective aspect ratio of the combined mudmat and superstructure. Collectively, the results of the present study provide insight into the inherent scour protection provided by a skirted mudmat foundation. Highlights: F0B7 Scour around subsea structures with mudmat foundations is explored experimentally. F0B7 Two modes of scour are observed, depending on relative structure size and mudmat size. F0B7 Mudmats reduce scour rates for both modes, but increase scour depth and extent. F0B7 Trends in scour are explained using the combined effective height of the structure and mudmat.